Perceptions and beliefs of Education students about learning at university and during the practicum: a qualitative study - Poveda, Belén; Barceló, María Luisa; Rodríguez Gómez, Inmaculada; López-Gómez, Ernesto (Revista Complutense de Educación, 2021)
Initial teacher training takes place in various contexts, mainly at university and in schools. In recent years, several studies have focused on the exploration of how learning takes place in these scenarios, considering perspectives, designs and various approaches to research. The current paper contributes to this line of research by addressing two objectives, namely: to analyze the perception of Education students about the type of learning that takes place at university and in the schools, during the practicum, and to explore their beliefs of effective connection. For this, a qualitative study has been carried out, based on the application of a questionnaire with open questions. The participants were 36 students from the third (58%) and fourth (42%) years of the Degrees in Early Childhood Education and Primary Education of the higher education institution that has been the object of study. The results show that students perceive the centrality of the practicum in their training process, although they highlight the importance of the learning that the university, as a context, provides. Four images of the university-practicum link emerge from the study, which may help understand the relationship between theory and practice: unidirectional, bidirectional, indirect or not very apparent, and breach or gap. The conclusions of the present study recommend rethinking the syllabus, in order to bring the reality of schools closer to university training, consider organizational aspects for the development of the practicum, and enhance narrative strategies during the practicum, from the standpoint of observation, analysis of situations, and reflective practice.